In vitro combinatory cytotoxicity of hepatocarcinogenic asarone isomers and flavonoids. (October 2019) - Uebel, Thomas; Wilken, Markus; Vu Chi, Hung; Esselen, Melanie
Abstract: Acorus calamus is a swamp herb, which is widely spread in northern hemisphere. It is used in infusions and in bitters but also in food supplements and in traditional herbal medicine. However, the main A. calamus ingredients, propenylic 2, 4, 5-trimethoxyphenylpropene isomers, termed alpha - ( trans ) and beta - ( cis ) asarone, are known carcinogens in rodents. Genotoxic and mutagenic properties are proposed. The presented in vitro cytotoxicity study focused on time-dependent and combinatory exposure scenarios. All experiments performed in HepG2 cells show moderate (in middle micromolar range) cytotoxicity with a time-dependent increase in effectiveness. The combination of the two asarone isomers in short time experiments (1 h) did not show any effect, whereas asarone isomer interaction changes from synergistic to antagonistic with an extended duration of exposure up to 72 h. The antagonism occurred predominantly in the naturally occurring trans / cis -asarone ratio of approximately 1:10. Combinatory cytotoxicity of asarones and selected, dietary relevant flavonoids in constant ratios was mainly attributed to flavonoid toxicity. Highlights: Moderate cytotoxicity of single asarone isomers in a time dependent manner in HepG2 cells Interaction of asarone isomers in combination changes from synergistic to antagonistic with prolonged incubation time. Combination of asarones with selected flavonoids does not result in lower cytotoxicity.